PERAN KEGIATAN TAHFIZH AL-QUR’AN DALAM MEMBENTUK KARAKTER RELIGIUS SANTRI DI PESANTREN MIFTAHUL HUSNA - Harahap, Panorangi; Nasution, Zulkipli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of Tahfizh Al-Qur'an activities in shaping the religious character of students at Miftahul Husna Islamic Boarding School. The research employs a qualitative approach with a field study design, including in-depth interviews, participatory observation, and document study to obtain comprehensive data. The data were analyzed inductively through data reduction, narrative presentation, and interpretation to understand the internalization of religious values through Tahfizh. The findings indicate that Tahfizh not only enhances memorization of the text but also serves as a medium for internalizing moral, spiritual, and positive character values such as discipline, responsibility, and sincerity. This suggests that well-structured Tahfizh practices oriented towards developing faith and morals effectively shape students' religious character. In conclusion, Tahfizh functions as a strategic instrument in Islamic education to instill noble character and cultivate students with strong religious character.